Global change effects on plankton community structure and trophic interactions in a Patagonian freshwater eutrophic system - Valiñas, Macarena Soledad (2017)
The short- and mid-term effects of a simulated global change scenario (i.e., Future) of increased nutrients, acidification, and solar radiation, in the presence or absence of grazers, were evaluated on a freshwater plankton community of Patagonia, Argentina. We used a cluster experimental design with microcosms incubated outdoors simulating the in situ (i.e., Present) and the Future conditions. Short-term changes in net productivity and respiration, together with mid-term changes in the community (abundance, biomass, and phytoplankton cell size) were measured. Phytoplankton had lower net productivity and higher respiration and zooplankton had, in general, higher respiration under the Future than that under the Present condition when organisms were exposed to UVR. The mid-term impacts of the Future condition were neither significant on zooplankton abundances, nor in phytoplankton abundances, biomass, and cell size. Nevertheless, the zooplankton–phytoplankton interaction strength was greater under the Future condition. Zooplankton exerted a strong top-down pressure, regardless of the experimental scenarios, grazing preferentially on small phytoplankton cells, thus decreasing their abundances and biomass. Overall, there were significant short-term impact of our Future global change scenario; however, its effects on mid-term time scales were not significant, and indeed, the zooplankton top-down pressure was the main driver that shaped the phytoplankton community.